2018
DOI: 10.1002/hipo.23060
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of 3D head direction information in the human brain

Abstract: Head direction cells are critical for navigation because they convey information about which direction an animal is facing within an environment. To date, most studies on head direction encoding have been conducted on a horizontal two‐dimensional (2D) plane, and little is known about how three‐dimensional (3D) direction information is encoded in the brain despite humans and other animals living in a 3D world. Here, we investigated head direction encoding in the human brain while participants moved within a vir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…The data analysis, which focused on neural adaptation effects in the fMRI signal in response to repeated presentations of the same heading (compared with orthogonal headings), revealed that the retrosplenial complex (i.e., BA31) alone was modulated by perceived heading (Figure 5c). More recently, it has been shown that heading sensitivity of the human retrosplenial complex applies not only to directions in the horizontal plane but also to those in the vertical plane (i.e., relative to locations above or below the observer; Kim & Maguire, 2019). Moreover, Vass and Epstein (2017) found that the retrosplenial complex retains its sensitivity to heading information even in tasks that require orienting oneself in imagined environments, producing highly similar results to those obtained in visual orientation tasks.…”
Section: Retrosplenial Complexmentioning
confidence: 78%
“…The data analysis, which focused on neural adaptation effects in the fMRI signal in response to repeated presentations of the same heading (compared with orthogonal headings), revealed that the retrosplenial complex (i.e., BA31) alone was modulated by perceived heading (Figure 5c). More recently, it has been shown that heading sensitivity of the human retrosplenial complex applies not only to directions in the horizontal plane but also to those in the vertical plane (i.e., relative to locations above or below the observer; Kim & Maguire, 2019). Moreover, Vass and Epstein (2017) found that the retrosplenial complex retains its sensitivity to heading information even in tasks that require orienting oneself in imagined environments, producing highly similar results to those obtained in visual orientation tasks.…”
Section: Retrosplenial Complexmentioning
confidence: 78%
“…Although Kim et. al 51 demonstrated that RSC activity is correlated with behavioral performance in three-dimensional space, how the use of distinct reference frames during navigation impacts RSC activity was still unclear. Remarkably, in this study, we found that RSC activity systematically covaried with behavioral responses, and that this correlation depended on the reference frame used.…”
Section: Discussionmentioning
confidence: 99%
“…Hodgetts et al (2017), using ultra-high field 7 T high-resolution fMRI, suggest that the subiculum has a particular role during scene, but not face or object, discriminations of previously learned scenes. Kim and Maguire (2018), again using fMRI, had subjects navigate in a 3D space, using a virtual “spaceship.” They found activations in the anterior thalamus and subiculum reflecting the horizontal component of 3D head direction (or “azimuth”), whereas retrosplenial cortex responded to the vertical component of 3D head direction (“pitch”). These data suggest a role for the subiculum in both mnemonic and spatial processing in humans.…”
Section: Spatial Coding By Neurons In the Main Hippocampal Output: Thmentioning
confidence: 99%
“…It has been known for some time that the anterodorsal nucleus of the thalamus contains a substantial population of head-direction cells (Blair and Sharp, 1995; Taube, 1995; Goodridge and Taube, 1997). These cells are thought to contribute to path integration (Frohardt et al, 2006), as well as mapping and navigation in 3D space (Laurens et al, 2016; Page et al, 2018; Angelaki et al, 2019; but see Taube et al, 2013; Shinder and Taube, 2019), the latter function potentially in association with retrosplenial cortex (Kim and Maguire, 2018). Meanwhile, head-direction cells have also been recorded in the anteroventral thalamic nucleus (Tsanov et al, 2011).…”
Section: Spatial Coding By Neurons In the Anterior Thalamic Nucleimentioning
confidence: 99%